2012
DOI: 10.1088/0957-4484/23/5/055703
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inter-tube distance and alignment on tunnelling resistance and strain sensitivity of nanotube/polymer composite films

Abstract: A model for carbon nanotube (CNT)/polymer composite conductivity is developed, considering the effect of inter-tube tunnelling through the polymer. The statistical effects of inter-tube distance and alignment on the tunnelling are investigated through numerical modelling, to highlight their role in the conductance and piezoresistance of the composite film. The impact of critical parameters, including the concentration, alignment and aspect ratio of the CNTs and the tunnelling barrier height of the polymer is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
103
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(110 citation statements)
references
References 25 publications
5
103
1
1
Order By: Relevance
“…Tunneling was regarded as the dominant mechanism that determined electromechanical behavior, and the change in resistance of individual CNTs when strained was excluded. It was shown that the model became less sensitive to strains with higher CNT concentrations, similar to what Rahman et al [17] found. More recently, Lee et al [18] formulated a 2D percolationbased CNT-network model that characterized the effects of CNT parameters (i.e., CNT length and density) on the electrical and electromechanical properties of the nanocomposite.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Tunneling was regarded as the dominant mechanism that determined electromechanical behavior, and the change in resistance of individual CNTs when strained was excluded. It was shown that the model became less sensitive to strains with higher CNT concentrations, similar to what Rahman et al [17] found. More recently, Lee et al [18] formulated a 2D percolationbased CNT-network model that characterized the effects of CNT parameters (i.e., CNT length and density) on the electrical and electromechanical properties of the nanocomposite.…”
Section: Introductionsupporting
confidence: 82%
“…In these studies, the morphological features of CNT-based nanocomposites were somewhat simplified during modeling [16][17][18], where most studies assumed that CNTs were straight and of uniform length, both of which are rarely true in actual nanocomposites. In fact, experimental studies [3,22] revealed that nanocomposites fabricated using different types of CNTs resulted in different electromechanical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…When the CNT-based nanocomposite model was subjected to uniaxial tensile strains to 7,000 µe, nonlinear strain sensing response was observed. Similarly, Rahman et al [38] simulated strain sensing response of a network of nanotubes modeled as straight elements while considering tunneling resistance. Linear piezoresistivity was observed during small strains (e < 0.01), but nonlinearity was observed at higher strains (0.2 < e < 1.5).…”
Section: Introductionmentioning
confidence: 99%
“…1 For the last ten years, the research on piezoresistive transducers has mainly been focused on the use of nanomaterials to optimize sensitivity, power consumption, and sensor miniaturization. For instance, Si nanowires, [2][3][4] carbon nanotubes, [5][6][7] graphene, [8][9][10] MoS 2 , 10 SiC nanoribbons, 11 Ag nanowires, 12 and metallic nanoparticle (NP) assemblies [13][14][15][16][17][18][19][20] have been exploited at the laboratory scale to achieve very large gauge factors (GFs) which rival the state-of-the-art bulk Si gauges. Although the use of nanomaterials has attracted a lot of attention in the literature these past few years, many technological obstacles (manipulation of individual nanostructures, complexity of the process, sensor reproducibility, etc.)…”
mentioning
confidence: 99%